Bibliography of the Athabasca River Basin (BARB) Poster Presentation - Elliott, Colin (2011)
An online, searchable bibliography of published materials relating to the Athabasca River Basin. BARB is intended to be a comprehensive resource for all researchers examining the Athabasca River Basin. A multidisciplinary approach ensures that the bibliography is extensive, detailed, and captures all activity within the basin.